Dietary absorption profile, bioavailability of (poly)phenolic compounds, and acute modulation of vascular/endothelial function by hazelnut skin drink. (December 2019) - Mocciaro, Gabriele; Bresciani, Letizia; Tsiountsioura, Melina; Martini, Daniela; Mena, Pedro; Charron, Melanie; Brighenti, Furio; Bentley, Stefano; Harvey, Matt; Collins, David; Del Rio, Daniele; Ray, Sumantra
Graphical abstract: Highlights: A hazelnut skin drink was tested in a single-blind, non-randomised unilateral cross-over trial. Ten plasma and twenty-four urine hazelnut phenolic metabolites were identified and quantified. Hazelnut skin phenolics were highly bioavailable. No acute beneficial effect of the test drink on endothelial function was observed. Abstract: Evidence supports an inverse association between nut consumption and cardiovascular disease (CVD) risk and (poly)phenols have been identified as potential co-mediators of these beneficial effects. This study investigated the acute absorption and the bioavailability of (poly)phenols of a hazelnut skin drink in healthy subjects and assessed its acute impact on vascular/endothelial function. A single-blind, non-randomised unilateral cross-over trial involved 41 healthy adults. Blood and urine were collected resulting in the detection of ten plasma and twenty-four urine metabolites. Bioavailability was estimated about 27%. The acute ingestion of the test drink did not show any statistically significant changes to vascular/endothelial function, although a trend was observed with high-producers of certain secondary metabolites. These results indicate that the hazelnut skin drink contains an important fraction of bioavailable bioactive compounds. However, no significant acute effects of the test drink on vascular/endothelial function were observed. The study has been registered on http://www.isrctn.com .